Lecturer Gender Perspective With Online Thesis Guidance Case Study Elista in Jambi University - Jefri Marzal; Suwannit Chareen Chit; Edi Elisa; Pradita Eko Prasetyo Utomo; Dwi Agus Kurniawan; Rizka Octavia Sandra (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
This research is a mixed method research using an explanatory design. The purpose of this study is to use Elista to assess a lecturer's response to thesis guidance based on the lecturer's gender. This study was condi-cted in Jambi University, involving 330 female and 359 male lecturers respectively. The sampling method used was purposive sampling technique, with the sample criterion being academics who became thesis su-pervisors. Interviews and surveys on Elista were conducted and the responses were gathered. The goal of this study is to establish a technology-based final project guidance system in which it is explored if the thesis supervisor's speedy response to guidance at Elista is affected by the gender of the thesis supervisor. The findings of the study demonstrate that female supervisors respond faster than male supervisors when em-ploying technology such as Elista to carry out the guidance procedure. Elista improves the effectiveness and efficiency of the guidance process between supervisors and students in terms of implementation.